Long-term follow-up of transsexual persons undergoing sex reassignment surgery: cohort study in Sweden. - Cecilia Dhejne (Public Library of Science (PLoS), 2011)
Context The treatment for transsexualism is sex reassignment, including hormonal treatment and surgery aimed at making the person's body as congruent with the opposite sex as possible. There is a dearth of long term, follow-up studies after sex reassignment. Objective To estimate mortality, morbidity, and criminal rate after surgical sex reassignment of transsexual persons. Design A population-based matched cohort study. Setting Sweden, 1973-2003. Participants All 324 sex-reassigned persons (191 male-to-females, 133 female-to-males) in Sweden, 1973-2003. Random population controls (10:1) were matched by birth year and birth sex or reassigned (final) sex, respectively. Main outcome measures Hazard ratios (HR) with 95% confidence intervals (CI) for mortality and psychiatric morbidity were obtained with Cox regression models, which were adjusted for immigrant status and psychiatric morbidity prior to sex reassignment (adjusted HR [aHR]). Results The overall mortality for sex-reassigned persons was higher during follow-up (aHR 2.8; 95% CI 1.8-4.3) than for controls of the same birth sex, particularly death from suicide (aHR 19.1; 95% CI 5.8-62.9). Sex-reassigned persons also had an increased risk for suicide attempts (aHR 4.9; 95% CI 2.9-8.5) and psychiatric inpatient care (aHR 2.8; 95% CI 2.0-3.9). Comparisons with controls matched on reassigned sex yielded similar results. Female-to-males, but not male-to-females, had a higher risk for criminal convictions than their respective birth sex controls. Conclusions Persons with transsexualism, after sex reassignment, have considerably higher risks for mortality, suicidal behaviour, and psychiatric morbidity than the general population. Our findings suggest that sex reassignment, although alleviating gender dysphoria, may not suffice as treatment for transsexualism, and should inspire improved psychiatric and somatic care after sex reassignment for this patient group.